Effects on IS1 transposition frequency of a mutation in the ygjD gene involved in an essential tRNA modification in Escherichia coli. Issue 2 (23rd August 2013) - Hashimoto, Chika; Hashimoto, Masayuki; Honda, Hirofumi; Kato, Jun‐ichi
Abstract: The YgjD protein is essential for the synthesis of the universal tRNA modification, N 6 ‐threonylcarbamoyladenosine (t 6 A), which is necessary for the decoding of ANN codons. We isolated a suppressor ( ygjD sup ) of the ygjD ts mutant by its permissive growth at high temperature in Escherichia coli . Resequencing of the ygjD sup mutant genome showed the presence of a complicated chromosome rearrangement, an inverse insertion of a large duplicated region ( c . 450 kb) into a small deleted region. The temperature‐resistant growth associated with ygjD sup was due to the presence of multicopy suppressor genes, yjeE and groL, of the ygjD ts mutation in the duplicated region. This DNA rearrangement was not simply mediated by IS 1 transposition, but the duplicated region was flanked by IS 1 . We showed that the frequency of IS 1 transposition was increased in ygjD ts mutants. The transposase of IS 1 is coded for by the insB gene, and its translation occurs through a frameshift of a ribosome translating upstream of the insA gene. We showed that this frameshifting frequency was increased by the ygjD ts mutation. These results indicated that the mutation of the gene for tRNA modification, t 6 A, affected IS 1 transposition.